TWIST1 is a molecular marker for a poor prognosis in oral cancer and represents a potential therapeutic target. Issue 3 (21st October 2013) - da Silva, Sabrina Daniela; Alaoui‐Jamali, Moulay A.; Soares, Fernando Augusto; Carraro, Dirce Maria; Brentani, Helena Paula; Hier, Michael; Rogatto, Silvia Regina; Kowalski, Luiz Paulo
Abstract : BACKGROUND: Locoregional recurrence and distant metastases are ominous events in patients with advanced oral squamous cell carcinoma (OSCC). The objective of this study was to identify functional biomarkers that are predictive of OSCC progression to metastasis. METHODS: The expression profile of a network of epithelial‐mesenchymal transition (EMT) genes was investigated in a large cohort of patients with progressive OSCC using a complimentary DNA microarray platform coupled to quantitative reverse transcriptase‐polymerase chain reaction and immunohistochemical analyses. Therapeutic potential was investigated in vitro and in vivo using an orthotopic mouse model of metastatic OSCC growing in the tongue microenvironment. RESULTS: Among deregulated EMT genes, the Twist‐related protein 1 ( TWIST1 ) transcription factor and several of its regulated genes were significantly overexpressed across advanced stages of OSCC. This result was corroborated by the clinical observation that Twist1 up‐regulation predicted the occurrence of lymph node and lung metastases as well as poor patient survival. In support of Twist1 as a driver of OSCC progression, the up‐regulation of Twist1 was observed in cells isolated from patients with metastatic OSCC. The inhibition of Twist1 in these metastatic cells induced a potent inhibition of cell invasiveness in vitro as well as progression in vivo. CONCLUSIONS: The current results provide evidence for the prognostic value and therapeutic potential of a network of Twist genes in patients with advanced OSCC. Cancer 2014;120:352–362 . © 2013 American Cancer Society . Abstract : A network of Twist genes is involved in oral squamous cell carcinoma invasiveness and predicts a poor patient outcome. Twist1 has potential therapeutic utility to prevent the progression of oral squamous cell carcinoma to metastasis.